2009
DOI: 10.1002/mds.22643
|View full text |Cite
|
Sign up to set email alerts
|

The PRIAMO study: A multicenter assessment of nonmotor symptoms and their impact on quality of life in Parkinson's disease

Abstract: We performed a multicenter survey using a semistructured interview in 1,072 consecutive patients with Parkinson's disease (PD) enrolled during 12 months in 55 Italian centers to assess the prevalence of nonmotor symptoms (NMSs), their association with cognitive impairment, and the impact on patients' quality of life (QoL). We found that 98.6% of patients with PD reported the presence of NMSs. The most common were as follows: fatigue (58%), anxiety (56%), leg pain (38%), insomnia (37%), urgency and nocturia (35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

86
793
8
44

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,217 publications
(970 citation statements)
references
References 33 publications
86
793
8
44
Order By: Relevance
“…41 Depending on the diagnostic methods used, apathy is diagnosed in 20-36% of new-onset patients who have not been treated with drugs. [42][43][44] In early-stage Parkinson's disease, apathy seems to decrease after introduction of dopaminergic treatment, but its frequency increases again to 40% in patients without dementia and to 60% in patients with dementia after 5-10 years of disease. [45][46][47][48] Apathy has been described mainly in the context of progressive cognitive deterioration in various neuro degenerative diseases, including Alzheimer's disease.…”
Section: Apathy In Parkinson's Disease Prevalence and Clinical Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…41 Depending on the diagnostic methods used, apathy is diagnosed in 20-36% of new-onset patients who have not been treated with drugs. [42][43][44] In early-stage Parkinson's disease, apathy seems to decrease after introduction of dopaminergic treatment, but its frequency increases again to 40% in patients without dementia and to 60% in patients with dementia after 5-10 years of disease. [45][46][47][48] Apathy has been described mainly in the context of progressive cognitive deterioration in various neuro degenerative diseases, including Alzheimer's disease.…”
Section: Apathy In Parkinson's Disease Prevalence and Clinical Relevancementioning
confidence: 99%
“…Apathy in Parkinson's disease has also been related to more severe motor impairment, worse executive dysfunction, and a higher risk of develop ing dementia than Parkinson's disease without apathy. 50,51 As such, apathy is a key symptom of the worsening of Parkinson's disease as the disease progresses, predictive of decreased functioning in activities of daily living, 52 decreased response to treatment, poor outcome, and diminished quality of life, 43,50,53 and it is a major contributor to caregiver emotional distress. 54 The multidimensional nature of apathy A patient started to develop symptoms of Parkinson's disease at age 46 years, with a prodromal phase characterised by a complete hypodopaminergic behavioural syndrome.…”
Section: Apathy In Parkinson's Disease Prevalence and Clinical Relevancementioning
confidence: 99%
“…For example, apathy, a common feature of PD (e.g., Barone, et al, 2009;Dujardin, et al, 2007;Pluck & Brown, 2002), contributes to impaired memory (e.g., Butterfield, Cimino, Oelke, Hauser, & Sanchez-Ramos, 2010) and future studies should be careful to control for this.…”
Section: Q12mentioning
confidence: 99%
“…Given that previous studies showed PD significantly affects the quality of sleep [14] and QoL [15,16], we used different scales to assess the incidence, degree and type of SD and their effect on QoL while taking into consideration various characteristics of PD [17][18][19]. The median PSQI score was 12, which was significantly higher in the group with PD than in the control group, where the median value was 4.…”
Section: Discussionmentioning
confidence: 99%